Plugging Cisterns, Cesspools, Septic Tanks, and Other Holes - Rogers, Danny H; Powell, G. Morgan (My University, 1998)
This publications explains how to plug cisterns, cesspools, septic tanks, and other holes.
MF2246_1997-07
Keywords: MF2246; Environment and Natural Resources; Equipment and structures.; MF